2020
DOI: 10.1111/ppa.13293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brassica napus–Leptosphaeria maculans interaction on the emergence of virulent isolates of L. maculans, causal agent of blackleg disease in canola

Abstract: Canola (Brassica napus) is the major oilseed crop in Canada. Blackleg (Leptosphaeria maculans) causes yield losses annually, with a larger impact in the last two decades caused by breakdown of resistance in growers’ fields. A 4‐year small‐plot field study from 2014 to 2017 in Manitoba investigated the impact of the B. napus–L. maculans interaction on the emergence of virulent isolates towards specific R genes. Doubled haploid B. napus ‘Topas’ introgression lines carrying single R genes were used, with a 2‐year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…These two examples, along with the Canadian Rlm3 breakdown example, show the impact major resistance genes can have on the L. maculans avirulence profile (Zhang et al, 2016). Rashid et al (2020) found a rapid loss of avirulence and shifts to virulence by L. maculans isolates in as little as 1 year in Canada. Identifying the blackleg major resistance genes within a cultivar becomes valuable to help properly steward and increase the longevity of the resistance genes (Van de Wouw and Howlett, 2019).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…These two examples, along with the Canadian Rlm3 breakdown example, show the impact major resistance genes can have on the L. maculans avirulence profile (Zhang et al, 2016). Rashid et al (2020) found a rapid loss of avirulence and shifts to virulence by L. maculans isolates in as little as 1 year in Canada. Identifying the blackleg major resistance genes within a cultivar becomes valuable to help properly steward and increase the longevity of the resistance genes (Van de Wouw and Howlett, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Under natural conditions, Kutcher et al (2013) reported disease severity levels of less than 0.5. Trials that are inoculated in Canada can still experience low disease severity levels of less than 1.0 ( Rashid et al, 2020 ). In comparison to provincial blackleg disease survey data, this study had higher disease incidence ( Canadian Plant Disease Survey, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deployment of blackleg-resistant cultivars is the most effective strategy for blackleg management [ 8 ]. However, the erosion or loss of resistance has been reported in many canola cultivars, reflecting the emergence of virulent isolates of L. maculans [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%